Opening doors understanding college reading - Cortina, Joe; Elder, Janet 1947-. (Boston McGraw-Hill, 2002)
[This book] is designed to help college students move from a pre-college reading level to a college reading level. It also presents a systematic way of approaching college textbook material that can make students more efficient in the study skills integral to their college success. While the scope of this book is broad, the focus is ultimately on comprehension. Comprehension skills are introduced early in the text and are integrated throughout subsequent chapters so that students learn how to apply them.-To the instructor.
Orientation, preparing and organizing yourself for success in college : making yourself successful in college ; Approaching college reading and developing a college-level vocabulary ; Approaching college assignments, reading textbooks and following directions -- Comprehension, understanding college textbooks by reading for ideas : determining the topic and the stated main idea ; Formulating implied main ideas ; Identifying supporting details ; Recognizing authors' writing patterns ; Reading critically ; Thinking critically -- Systems for studying textbooks, developing a system that works for you : selecting and organizing textbook information ; Rehearsing textbook information and preparing for tests -- Appendixes : an introduction to using computers, the Internet, and the World Wide Web ; Glossary of key terms ; A list of word parts ; World map.
Keywords: College readers; Reading (Higher education).